Desert small mammal responses to wildfire and predation in the aftermath of a La Nińa driven resource pulse. (4th June 2013) - Letnic, Mike; Tischler, Max; Gordon, Christopher
Abstract In arid Australia, flooding rains associated with the La Nińa phase of El Niño/Southern Oscillation (ENSO) prompt dramatic pulses of primary productivity, which in turn result in irruptions of rodents and their predators. When it is dry, the dense vegetation produced by extreme rainfall events can fuel extensive wildfires. In this study we investigated the effects of a wildfire that followed exceptional rainfalls associated with the La Niña event of 2010–2011 on small mammal assemblages in a stony (gibber) desert ecosystem in central Australia. When the study commenced in July 2011, there was dense grass cover and rodents, particularly, Rattus villosissimus occurred at high abundance. Mammalian predator activity was high throughout the study period and predators primarily consumed rodents. A wildfire in October 2011, reduced grass cover but there was no effect of fire on the abundance or species richness of small mammals, immediately after the wildfire or 11 months after the wildfire. Following the fire event, grass cover increased on both burnt and unburnt grids, but did not reach the levels recorded prior to the wildfire. Small mammal abundance and species richness declined steadily during the study irrespective of the occurrence of wildfire. At 6 and 11 months after the wildfire there was no difference in grass cover on burnt and unburnt grids and Rattus villosissimus were absent. Our results show that the removal of vegetation by wildfire was not a major driver of small mammal assemblage structure in this stony desert ecosystem. Our results are consistent with the predictions of ecosystem organization models that describe switching trophic control along gradients of resource productivity and support the notion that the decline of small mammals was driven by the onset of top‐down control by abundant predators coupled with diminished availability of food resources.